Points of Equilibrium: Religious Beliefs and Economic Development Policy. (26th February 2016) - Clarke, Matthew
Abstract: Eighty per cent of the world's population professes religious belief. Such beliefs provide precepts on how individuals should conduct their private lives and (often) how society should be organized. Given there are 2.1 billion Christians worldwide and 1.3 billion Muslims, understanding the religious approach to social life based on sacred texts and social teachings of Christianity and Islam has a strong relevance to those interested in implementing international economic development policies. This paper argues that religion can thus play a positive role in development and specifically support development economic policies at the international level. The purpose of this paper is not to present a fully formed development economic policy, but rather to identify teachings of the world's two largest religions – such as preferencing the poor, minimizing inequality and having the economy serve wider realms of society – that directly speak to how sustainable economic development is understood within these faith traditions and how these teachings could scaffold and support and international policy frameworks aimed to achieve sustainable economic development. Copyright © 2016 John Wiley & Sons, Ltd and ERP Environment